FORMULATION DESIGN AND OPTIMIZATION OF ORAL FLOATING MATRIX TABLETS OF CIPROFLOXACIN HCL BY USING HPMC AND XANTHAN GUM WITH EXPERIMENTAL DESIGN - Pasa, Gourishyam; Choudhury, Prasanta Kumar; Panigrahi, Ghanshyam (Asian Journal of Pharmaceutical Research and Development, 2018)
The oral floating matrix tablets of Ciprofloxacin Hydrochloride were formulated by Experimental design by using HPMC K100M and Xanthan gum as the retardant polymers each with three different levels with an approach to increase gastric residence and thereby improve drug bioavailability. From FTIR results confirm the absence of chemical interaction between the drug with the excipients used in tablet formulations. Also, there was no shift in the endotherm of in the drug- excipients mixtures indicating compatibility of drug with all the excipients. All the tablets were prepared by effervescent approach in which Sodium bicarbonate was added as a gas generating agent. Floating Matrix tablets were prepared by direct compression method and prepared tablets were evaluated for weight variation, percentage friability, hardness and drug content studies. All the formulations showed compliance with pharmacopeia standards. Floating lag times of all the formulations were within 1 minute and Total floating time of all the formulations were more than 12 hours. In vitro release studies revealed that the release rate decreased with increase polymer proportion of retarding polymers. The formulation CHX8 sustained release of drug for 12 hrs with 20% release of drug after 1hr and more than 97% at the end of 12 hrs. From the Kinetic model it was found that the optimized formulation CHX8 showed linearity in case of Zero order (R2: 0.952) and Higuchi model (R2: 0.948). By fitting data to Korsmeyer-Peppas model and ‘n’ value lying above 0.5 indicating non Fickian release.